PENGENALAN POTENSI BAHAYA KEBAKARAN SEBAGAI TINDAKAN PENCEGAHAN KECELAKAAN KERJA PADA PEGDAGANG SEKEN SEPEDA LISTRIK DI KELURAHAN X KOTA BATAM - Noviyanti Noviyanti (COVIT (Community Service of Health), 2022)
Fire is an unwanted event for everyone and fires can also be fatal. Fires can occur anywhere and anytime, in places or buildings that are at risk of fire hazards (Ramli, 2010). One of the interventions that can be done to overcome the risk of fire is the introduction of potential fire hazards and their prevention measures. The purpose of this service is to provide knowledge about the introduction of potential fire hazards to used electric bicycle traders in Tanjung Sengkuang Batam. This service is carried out for approximately one month. This service program has several activities, namely identification, and implementation of counseling for electric bicycle traders. This service is carried out at a used electric bicycle dealer in ward, Batam. It was found that some bicycle traders still do not know about the risks that will arise from electric bicycles and their preventive measures by using tools such as a light fire extinguisher (Apar). The output of this service is an increase in public knowledge about the risk of fire and what actions will be taken. The advice given to the puskesmas is to make a program related to Occupational Health and Safety (K3), especially regarding the risk of fire, preventive measures, and personal protective equipment (PPE) used by traders when working. Keywords: Fire, Secondhand Trader, Electric Bike